2016
DOI: 10.1111/evo.13142
|View full text |Cite
|
Sign up to set email alerts
|

Coloniality and migration are related to selection on MHC genes in birds

Abstract: The major histocompatibility complex (MHC) plays a key role in pathogen recognition as a part of the vertebrate adaptive immune system. The great diversity of MHC genes in natural populations is maintained by different forms of balancing selection and its strength should correlate with the diversity of pathogens to which a population is exposed and the rate of exposure. Despite this prediction, little is known about how life-history characteristics affect selection at the MHC. Here, we examined whether the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 96 publications
5
38
1
Order By: Relevance
“…It is possible, however, that combinations of rare alleles may be associated with decreased infection in FL, but our sample sizes are too small to test for such an association. Overall, our results for class I are consistent with the hypothesis that migratory behaviour is associated with increased MHC diversity, as suggested by comparative studies (Buehler et al ., ; Minias et al ., ), and a comparison of closely related migratory and resident warbler species (Richardson & Westerdahl, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible, however, that combinations of rare alleles may be associated with decreased infection in FL, but our sample sizes are too small to test for such an association. Overall, our results for class I are consistent with the hypothesis that migratory behaviour is associated with increased MHC diversity, as suggested by comparative studies (Buehler et al ., ; Minias et al ., ), and a comparison of closely related migratory and resident warbler species (Richardson & Westerdahl, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about how life‐history traits, that may affect exposure to parasites, are related to MHC variation (Šimková et al ., ). The results of a recent comparative study of nonpasserine birds showed that MHC class I diversity was positively associated with both coloniality and migratory behaviour across species (Minias et al ., ), suggesting that these traits play an important role in shaping genetic variation at MHC genes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite recent advances (Minias, et al 2017;O'Connor, et al 2018), it remains generally 72 unknown how pathogen-mediated selection affects immune gene evolution across species. Do signatures of positive selection mostly evolve convergent, or do they evolve divergent 74 depending on pathogen exposure and life-history trade-offs?…”
Section: Introduction 48mentioning
confidence: 99%